Programmed cell death and Salmonella pathogenesis: an interactive overview - Zhang, Yu; Xu, Maodou; Guo, Yujiao; Chen, Li; Vongsangnak, Wanwipa; Xu, Qi; Lu, Lizhi (Frontiers in Microbiology, 2024)
Abstract：Programmed cell death (PCD) is the collective term for the intrinsically regulated death of cells. Various types of cell death are triggered by their own programmed regulation during the growth and development of organisms, as well as in response to environmental and disease stresses. PCD encompasses apoptosis, pyroptosis, necroptosis, autophagy, and other forms. PCD plays a crucial role not only in the growth and development of organisms but also in serving as a component of the host innate immune defense and as a bacterial virulence strategy employed by pathogens during invasion. The zoonotic pathogen Salmonella has the ability to modulate multiple forms of PCD, including apoptosis, pyroptosis, necroptosis, and autophagy, within the host organism. This modulation subsequently impacts the bacterial infection process. This review aims to consolidate recent findings regarding the mechanisms by which Salmonella initiates and controls cell death signaling, the ways in which various forms of cell death can impede or restrict bacterial proliferation, and the interplay between cell death and innate immune pathways that can counteract Salmonellainduced suppression of host cell death. Ultimately, these insights may contribute novel perspectives for the diagnosis and treatment of clinical Salmonella-related diseases.